The Effect of Using Audiovisual Media on Students' Learning Interest in Islamic Religious Education at SMP Muhammadiyah 57 Medan - Husein, Mhd Iqbal; Setiawan, Hasrian Rudi (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2025)
This study examines the effect of using audiovisual media on students' learning interest in Islamic Religious Education (IRE) at SMP Muhammadiyah 57 Medan. The research aims to determine whether the integration of audiovisual media in IRE lessons can enhance students' motivation and engagement in learning. The study employs a quantitative approach with a pre-test and post-test design, involving 100 students as participants. The data collected through questionnaires and tests were analyzed using descriptive and inferential statistics. The results show a significant increase in students' learning interest after the implementation of audiovisual media in the classroom. The findings suggest that audiovisual media effectively captures students' attention and stimulates their interest in IRE, leading to improved learning outcomes. This study highlights the importance of incorporating innovative teaching methods, such as audiovisual media, in enhancing the quality of education and fostering greater student engagement.